PARTISIPASI POLITIK MASYARAKAT DALAM PEMILIHAN BUPATI DAN WAKIL BUPATI MUNA TAHUN 2020 - La Linus; Farid Yusuf Nur Achmad; Nastia Nastia; Herman Lawelai (Universitas Islam Darul Ulum Lamongan, 2022)
This study aims to determine of Community Political Participation in the Election of Regent and Deputy Regent of Muna in 2020 in Parigi District, Muna Regency. This research is a descriptive study with a quantitative approach, which is a research method used to state the status of natural objects where the researcher acts as the main instrument. Voter's political participation, according to the findings, voting, administering a campaign, working in an election, seeking support for a candidate, or any activity that affects the outcome of the electoral process. in terms of political involvement Socialization has a direct influence on people's political participation in elections. Political education can influence political awareness, enabling individuals to choose and understand the importance of politics. In addition, knowledge and trust in government play an important role in shaping community engagement, with individuals exercising their right to vote if they have awareness and trust in the government. However, citizens' lack of understanding of their rights and obligations as citizens is a major problem. One reason for poor community engagement is a lack of trust in government. Political involvement in society can be influenced by social and economic factors in the political environment, and people trusted by the community can have a good impact on society by realizing the importance of political participation.